2011
DOI: 10.4238/2011.december.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of two consecutive carotenoid cleavage dioxygenase genes in strigolactone biosynthesis in plants

Abstract: ABSTRACT. Strigolactones are newly discovered plant hormones that perform various functions, from signaling in symbiotic interactions with arbuscular mycorrhizal fungi to controlling outgrowth of axillary buds. We examined the phylogenetic relationships of two carotenoid cleavage dioxygenase genes (CCD7 and CCD8) that are involved in consecutive upstream steps of the proposed strigolactone biosynthesis pathway. The CCD7 and CCD8 sequences from 11 model species, divided into two clades, correspond to sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The results from the current study showed that at least two DgCCD7 cDNAs exist in chrysanthemum. In all CCDs, exon/intron organization is conserved and the number of exons in CCD7 ranges from 6 to 9 in dicotyledon species (Wang et al, 2011 ). As we only isolated one clone from genomic DNA, the reason for the missing exon in DgCCD7b may due to alternative splicing (Wang et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from the current study showed that at least two DgCCD7 cDNAs exist in chrysanthemum. In all CCDs, exon/intron organization is conserved and the number of exons in CCD7 ranges from 6 to 9 in dicotyledon species (Wang et al, 2011 ). As we only isolated one clone from genomic DNA, the reason for the missing exon in DgCCD7b may due to alternative splicing (Wang et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In all CCDs, exon/intron organization is conserved and the number of exons in CCD7 ranges from 6 to 9 in dicotyledon species (Wang et al, 2011 ). As we only isolated one clone from genomic DNA, the reason for the missing exon in DgCCD7b may due to alternative splicing (Wang et al, 2011 ). With functional complementation of max3-9 mutants, subcellular localization in the plastid stroma and β-carotene cleavage of DgCCD7a supported a conserved function.…”
Section: Discussionmentioning
confidence: 99%
“…The first one, CCD7, is a stereo-specific dioxygenase that cleaves to only 9- cis -β-carotene to produce 9- cis -β-apo-10'-carotenal, which is subsequently cleaved by CCD8 to produce carlactone ( Figure 1 a). Genes that encode both CCDs have been identified in many different plant species, including primitive moss [ 32 , 33 ]. Analyses of Arabidopsis and rice plants that have mutations in the genes that encode CCD7 ( MAX3 —At2g42620; D17 / HTD1 —Os04g0550600) and CCD8 ( MAX4 —At4g32810— D10 , Os01g0746400) revealed a highly-branched phenotype, which is characteristic for strigolactone mutants that was reversible after treatment with a strigolactone analogue [ 5 , 34 , 35 , 36 , 37 ] ( Figure 1 b).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, carotenoids have a paramount ecological function because they act as attractants for pollinators and seed dispersal agents [13]. Furthermore, oxidative cleavage of carotenoids by a family of carotenoid cleavage dioxygenases (CCDs; enzymes that cleave double bonds) leads to the production of apocarotenoids, compounds with a variety of biological important activities such as phytohormones (ABA, and strigolactones, a group of terpene lactones with hormone activity that promote germination of root parasitic plants, stimulate symbiotic interactions between plants and arbuscular mycorrhizal fungi, and inhibit shoot axillary branching), the visual and signaling molecules retinal (chromophore of various visual pigments in animals) and retinoic acid (nuclear receptor ligand that is a major signal controlling a wide range of transcriptional processes), and the aromatic volatiles β-ionone (pollinator attractant and fruit or vegetable flavor), β-cyclocitral, geranial, geranyl acetone, theaspirone, α-damascenone and β-damascenone responsible for the flavor and aroma/scent of a number of flowers and a diversity of foods [1416]. …”
Section: Introductionmentioning
confidence: 99%